Regulation of GLUT4 gene expression by SREBP-1c in adipocytes - Im, Seung-Soon; Kwon, Sool-Ki; Kang, Seung-Youn; Kim, Tae-Hyun; Kim, Ha-Il; Hur, Man-Wook; Kim, Kyung-Sup; Ahn, Yong-Ho (Biochemical journal, 2006)
Expression of the GLUT4 (glucose transporter type 4 isoform) gene in adipocytes is subject to hormonal or metabolic control. In the present study, we have characterized an adipose tissue transcription factor that is influenced by fasting/refeeding regimens and insulin. Northern blotting showed that refeeding increased GLUT4 mRNA levels for 24 h in adipose tissue. Consistent with an increased GLUT4 gene expression, the mRNA levels of SREBP (sterol-regulatory-element-binding protein)-1c in adipose tissue were also increased by refeeding. In streptozotocin-induced diabetic rats, insulin treatment increased the mRNA levels of GLUT4 in adipose tissue. Serial deletion, luciferase reporter assays and electrophoretic mobility-shift assay studies indicated that the putative sterol response element is located in the region between bases −109 and −100 of the human GLUT4 promoter. Transduction of the SREBP-1c dominant negative form to differentiated 3T3-L1 adipocytes caused a reduction in the mRNA levels of GLUT4, suggesting that SREBP-1c mediates the transcription of GLUT4. In vivo chromatin immunoprecipitation revealed that refeeding increased the binding of SREBP-1 to the putative sterol-response element in the GLUT4. Furthermore, treating streptozotocin-induced diabetic rats with insulin restored SREBP-1 binding. In addition, we have identified an Sp1 binding site adjacent to the functional sterol-response element in the GLUT4 promoter. The Sp1 site appears to play an additive role in SREBP-1c mediated GLUT4 gene upregulation. These results suggest that upregulation of GLUT4 gene transcription might be directly mediated by SREBP-1c in adipose tissue.